Aplikasi klorheksidin glukonat 2%pada dentin tidak mempengaruhi kuat rekat geserkomposit resinyangmenggunakansistem adesif self etch (2% Chlorhexidine gluconate application on dentine does not affect bond strength of resin composite using self etch adhesive system) - Dewi Puspitasari; Andi Soufyan; Ellyza Herda (Journal of Dentomaxillofacial Science, 2014)
Composite resin is a widely used aesthetic restoration. The restoration can fail due to secondary caries. Chlorhexidinegluconate 2% is used as a cavity disinfectant to eliminate microorganisms on the prepared cavity and to prevent thesecondary caries. The purpose of this study was to analyze the effect of chlorhexidine gluconate 2% to the bondstrength of composite resin with self etch system adhesive on dentine. Sixteen specimens of buccal dentine of premolarscrown are divided into 2 different groups. Group I: Clearfil SE Bond self-etch primer was applied for 20 seconds,Clearfil SE Bond bonding was applied for 5 seconds and polymerized for 10 seconds. Composite resin was constructedincrementally and polymerized for 20 seconds. Group II: prior to self etch primer application as in group I,chlorhexidine gluconate 2% was applied for 15 seconds. Shear bond strength was tested using Testing machine andanalyzed with unpaired T test. The highest shear bond strength was obtained by applying chlorhexidine gluconate 2%.The study concludes that chlorhexidine gluconate 2% application to dentine did not affect significantly to the bondstrength composite resin using self etch adhesive systems.